2014
DOI: 10.1161/jaha.114.001363
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Cinacalcet on Atherosclerotic and Nonatherosclerotic Cardiovascular Events in Patients Receiving Hemodialysis: The EValuation Of Cinacalcet HCl Therapy to Lower CardioVascular Events (EVOLVE) Trial

Abstract: BackgroundPremature cardiovascular disease limits the duration and quality of life on long‐term hemodialysis. The objective of this study was to define the frequency of fatal and nonfatal cardiovascular events attributable to atherosclerotic and nonatherosclerotic mechanisms, risk factors for these events, and the effects of cinacalcet, using adjudicated data collected during the EValuation of Cinacalcet HCl Therapy to Lower CardioVascular Events (EVOLVE) Trial.Methods and ResultsEVOLVE was a randomized, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 32 publications
2
66
1
2
Order By: Relevance
“…Furthermore, in the HEMO (Hemodialysis) and 4D (Deutsche Diabetes Dialyse Studie) trials, 22% and 26% of deaths, respectively, were sudden (20,21 ). In the EVOLVE [EValuation Of Cinacalcet Hydrochloride (HCl) Therapy to Lower CardioVascular Events] trial, the largest randomized dialysis trial, which enrolled 3883 hyperparathyroid HD patients, 25% of deaths were adjudicated as sudden deaths (22 ). The recently initiated WED-HED (Wearable Cardioverter Defibrillator in Hemodialysis Patients; NCT02481206) study is a randomized controlled trial testing the efficacy of wearable defibrillators for the prevention of SCD in incident HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the HEMO (Hemodialysis) and 4D (Deutsche Diabetes Dialyse Studie) trials, 22% and 26% of deaths, respectively, were sudden (20,21 ). In the EVOLVE [EValuation Of Cinacalcet Hydrochloride (HCl) Therapy to Lower CardioVascular Events] trial, the largest randomized dialysis trial, which enrolled 3883 hyperparathyroid HD patients, 25% of deaths were adjudicated as sudden deaths (22 ). The recently initiated WED-HED (Wearable Cardioverter Defibrillator in Hemodialysis Patients; NCT02481206) study is a randomized controlled trial testing the efficacy of wearable defibrillators for the prevention of SCD in incident HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the EVOLVE trial has not shown that cinacalcet improves survival in ESRD patients, a post hoc analysis suggests that this drug that lowers PTH may also lower the risk of sudden cardiac death and/or cardiac failure [69]. …”
Section: Lvh Management In Ckd and Esrd Patients: Key Messagesmentioning
confidence: 99%
“…3 Hirahata Clinic, Tokyo, Japan. 4 Department of Cardiovascular Medicine, Toho University Ohashi Medical Center, Tokyo, Japan.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Although the underlying mechanism of the cardio-renal axis in patients with chronic kidney disease (CKD) has been determined in considerable detail over the past decade [1], cardiovascular disease is still a leading cause of death in maintenance dialysis patients worldwide [2,3] and also in Japan [4]. The accelerated progression of atherosclerosis during the conservative phase of CKD, before starting dialysis therapy [5], is thought to be one of the causes of the high incidence of cardiovascular events in the dialysis phase [6,7].…”
Section: Introductionmentioning
confidence: 99%